2017
DOI: 10.4067/s0718-95162017005000019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different tillage practices on soil physical properties, nitrate leaching and yield attributes of maize (Zea mays L.)

Abstract: Tillage, undoubtedly, is one of the most crucial practices to ameliorate crop productivity and maintain soil health.A field experiment was conducted at research farms; Institute of Soil and Environmental Sciences, University of Agriculture, Faisalabad, Pakistan to examine how soil properties and maize crop respond to different tillage strategies (minimum, conventional and deep tillage). Randomized complete block design (RCBD) was finalized for the experiment with three repeats. Maximum total biomass production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 12 publications
3
13
1
Order By: Relevance
“…The data obtained also show that the NT treatment with the highest N and P fertilization (N 3 P 3 ) presents a lower bulk density value (1.31 g cm -3 ) and a higher water storage capacity (22.17 %) than the CT-N 3 P 3 treatment, with values of 1.41 g cm -3 and 15.29%, respectively; however, no statistical differences were observed. This trend has been well documented in other research sites (Khan et al, 2017;Tormena et al, 2017).…”
Section: Effects Of Tillage Systems and Fertilizer Rates On Soil Physsupporting
confidence: 78%
See 1 more Smart Citation
“…The data obtained also show that the NT treatment with the highest N and P fertilization (N 3 P 3 ) presents a lower bulk density value (1.31 g cm -3 ) and a higher water storage capacity (22.17 %) than the CT-N 3 P 3 treatment, with values of 1.41 g cm -3 and 15.29%, respectively; however, no statistical differences were observed. This trend has been well documented in other research sites (Khan et al, 2017;Tormena et al, 2017).…”
Section: Effects Of Tillage Systems and Fertilizer Rates On Soil Physsupporting
confidence: 78%
“…No-tillage (NT) is one of the soil conservation practices that effectively controls soil erosion, with other widely recognized beneficial effects (Khan et al, 2017). There is scarce published information on the use of no-till farming in Ecuador, but the studies conducted during the past few years indicate there is a tendency towards improved yields with NT in volcanic highland soils.…”
Section: Introductionmentioning
confidence: 99%
“…These all could be due to intensive use of conventional practices in IGP. In an investigation, Ramos et al and Khan et al [8,9] concluded that traditional soil management practices effect the nutrients volume in soil and availability to plant for better production. RWCS in IGP produces around 10 to 12 Mg-ha residues [10,11] which were taken off or burned before sowing of the next crop.…”
Section: Introductionmentioning
confidence: 99%
“…Conservation tillage systems increased in use from 5.3 to 106 million ha between 1990 and 2009 ( Kassam et al, 2009 ). Research has shown that conservation tillage can improve soil structures ( Eden et al, 2020 ), SOC contents ( Guo et al, 2020 ), and water retention capacities ( He et al, 2009 ; Yang et al, 2020 ), reduce wind ( Gao et al, 2016 ) and water ( Bertol et al, 2003 ) erosion, and improve the physical properties of soils ( Khan et al, 2017 ). Currently, conservation tillage is widely used around the world, and in some areas of China, NT and subsoiling (SS) are especially common.…”
Section: Introductionmentioning
confidence: 99%